What is needed to successfully implement the EU HTA Regulation enabling broad patient access in Europe - Oriol Solà-Morales; Iga Lipska; Francois Meyer; Pier-Luigi Canonico; Herbert Altmann (Global & Regional Health Technology Assessment)
There has been a lot of discussion on the technical aspects of the soon to be implemented European Union’s Health Technology Assessment (EU HTA) regulation. However, there has been limited discussion on the implementation aspects and the potential limitations from a policy perspective. In May 2024, a group of HTA experts with previous policy responsibilities met in Rome to propose some policy aspects to be considered.